Absence of first‐pass isolation is associated with poor pulmonary vein isolation durability and atrial fibrillation ablation outcomes. Issue 6 (6th September 2021) - Ninomiya, Yuichi; Inoue, Koichi; Tanaka, Nobuaki; Okada, Masato; Tanaka, Koji; Onishi, Toshinari; Hirao, Yuko; Oka, Takafumi; Inoue, Hiroyuki; Takayasu, Kohtaro; Nakamaru, Ryo; Kitagaki, Ryo; et al.
Abstract: Background: Pulmonary vein (PV) reconnection is the main cause of atrial fibrillation (AF) recurrence. This study aimed to examine the effect of first‐pass PV isolation (PVI) on PV reconnection frequency during the procedure and on AF ablation outcomes. Methods: This retrospective study included 446 patients with drug‐refractory AF (370 men, aged 64 ± 10 years) who underwent initial PVI using an open‐irrigated contact force catheter between January 2015 and October 2016. We investigated the effect of first‐pass PVI on PV reconnection during spontaneous PV reconnection and dormant conduction after an adenosine triphosphate challenge. Results: First‐pass PVI was achieved in 69% (617/892) of ipsilateral PVs, of which we observed PV reconnection during the procedure in 134 (22%) PVs. This value was significantly lower than that observed in those without first‐pass PVI (50%, 138/275) ( P  < .0001). We divided the subjects into two groups based on the presence or absence of first‐pass PVI in at least one of two ipsilateral PVs: first‐pass (n = 383, 86%) and non‐first‐pass groups (n = 63, 14%). The 2‐year AF recurrence‐free rate was significantly higher in the first‐pass group than in the other group (75% vs 59%, log‐rank P  = .032). In 78 patients with repeat AF ablation, the PV reconnection rate in the second procedure was significantly lower in PVs that had first‐pass isolation in the first procedure (34% vs 73%, P  < .0001). Conclusions: Absence of first‐pass PVI was associated with a higher frequency of spontaneous PV reconnection and dormant conduction and poor ablation outcomes. First‐pass isolation may be a useful marker for better PVI durability. Abstract : The 2‐year AF recurrence‐free rate was significantly higher in the first‐pass group than in the other group (75% vs. 59%, log‐rank P = 0.032). Absence of first‐pass PVI was associated with a higher frequency of spontaneous PV reconnection and dormant conduction and poor ablation outcomes. First‐pass isolation may be a useful marker for better PVI durability.